An Upper Cretaceous paleo-aquifer system in the Eromanga Basin of the central Gawler Craton, South Australia: evidence from apatite fission track thermochronology. Issue 3 (2nd April 2016) - Boone, S. C.; Seiler, C.; Reid, A. J.; Kohn, B.; Gleadow, A.
ABSTRACT: An apatite fission track (AFT) study of crystalline basement in the central Gawler Craton reveals apparent ages in the range of ca 430–58 Ma. The majority of samples underwent protracted monotonic cooling related to regional Paleozoic exhumation, consistent with long-term crustal stability as expected for cratonic interiors. However, multiple samples show evidence of Late Cretaceous–early Paleogene reheating, indicating a more dynamic low-temperature history. Inverse time–temperature modelling of AFT data indicates varying degrees of thermal overprinting between ∼60 and 110°C, with substantially overprinted and negligibly overprinted samples in close proximity (<1 km). Time–temperature histories for samples that experienced thermal overprinting reveal localised Late Cretaceous–early Paleogene ( ca 100–50 Ma) heating that is significantly younger than the Paleozoic–early Mesozoic exhumation recorded regionally. The highly localised nature and non-systematic patterns of overprinting combined with the lack of major Mesozoic or Cenozoic fault structures are not consistent with a regional thermal event associated with substantial reburial and later exhumation. Rather, localised reheating was most likely caused by heated groundwater from the once-overlying Mesozoic Eromanga Basin aquifer system, whose modern discharge margin (∼400 km north of the study area) is marked by thermal mound springs that produce fluids with temperatures up to 100°C. Only basement rocks in close proximity to fluid pathways in the overlying aquifer would have recorded reheating, resulting in the observed sporadic distribution of partially overprinted samples. Thermal history modelling indicates rejuvenated apatite grains cooled to near-surface temperatures in the latest Cretaceous–Paleogene. This was likely in response to local removal of the overlying Eromanga Basin aquifer unit due to a relatively minor degree of exhumation (≤1 km) recorded regionally, which consequently disrupted the anomalous heating mechanism. These results show that the flow of heated groundwater is a feasible reheating mechanism for low-temperature thermochronometers, resulting in cooling patterns that may become decoupled from exhumation in cratonic interiors.